Using Blockchain to Strengthen Women's Rights in Developing Societies A Case Study of an Online University - Khalili, Barge Gul; Popalzay, Farida; Sharifi, Najia; Sultani, Ziagul (Pancasila International Journal of Applied Social Science, 2025)
The study investigates the potential of blockchain technology in empowering women in developing societies, particularly through enhancing secure digital identities, financial independence, and educational opportunities. In many developing countries, women face significant challenges accessing secure digital services, financial systems, and higher education. Blockchain, known for its transparency, security, and decentralization, presents a promising solution to these challenges. The primary purpose of this research is to evaluate the impact of blockchain technology on improving these areas, with a focus on online education. The research adopts a quantitative approach, utilizing a survey questionnaire to collect data from 120 women aged 20-25 from three faculties: Economics (50), Computer Science (50), and Education (20) in an online university. The data is analyzed using descriptive statistics, including percentages and mean scores, to assess women's perceptions of blockchain technology's benefits in securing digital identities, facilitating financial independence, and enhancing access to education. The results show that blockchain technology has the potential to significantly improve women's access to secure digital identities and financial services, thereby promoting financial independence and reducing gender disparities in education. However, barriers such as high implementation costs remain a significant challenge to widespread adoption. In conclusion, while blockchain technology offers a promising solution for women's empowerment in developing societies, further research and investment are needed to address its implementation challenges and ensure its accessibility for all women.